Предмет: Алгебра, автор: maxlarcov74

Вычислите значение выражения: (3√3)^2+(√3/3)^(-4)+√(6+√11) ∙√(6-√11)

Ответы

Автор ответа: Evgenia4836
1

Ответ:

Объяснение:

=(√27)²+(3/√3)⁴+√(6²-√11²)= 27+9+5= 41

Автор ответа: Universalka
0

(3\sqrt{3})^{2} +(\frac{\sqrt{3}}{3})^{-4}+\sqrt{6+\sqrt{11}}*\sqrt{6-\sqrt{11}}=(\sqrt{9*3})^{2}+(\frac{1}{\sqrt{3}})^{-4}+\sqrt{(6+\sqrt{11})(6-\sqrt{11})}=(\sqrt{27})^{2}+(\sqrt{3})^{4}+\sqrt{6^{2}-(\sqrt{11})^{2}} =27+9+\sqrt{36-11}=36+\sqrt{25}=36+5=41\\\\Otvet:\boxed{41}

Похожие вопросы